Role of Social Capital and Financial Wellbeing in Reaching Successful Entrepreneurial Financial Performance: A Moderated-Mediated Model of Financial Intelligence - Yao, Lei; Meng, Da (Frontiers in Psychology, 2022)
Financial well-being is an emerging variable in business psychology that is expected to measure the overall financial status and future financial trajectories. Financial intelligence and well-being have been key determining factors for the financial performance of entrepreneurs. The present study aimed to examine the crucial financial determinants (financial well-being and financial intelligence) and social capital factors for the entrepreneurial intentions and their financial performances among the 326 entrepreneurs in China. The findings of the study showed that the key financial indicators and social capital are significantly related to entrepreneurial intentions, which considerably predict the entrepreneurial financial performance. The mediating relationships also reported that entrepreneurial intentions and financial intelligence significantly mediate the relationship among social capital, financial well-being and entrepreneurial financial performance. The present study has highlighted the implications for the potential entrepreneurs for improving their financial performance through sustainable social capital, financial well-being and financial intelligence. This study will also help the strategists in screening the individuals for registering as entrepreneurs based on their financial intelligence quotient. The present study enriches the literature by offering an integrated model on financial well-being and entrepreneurial financial performance.